WORD-SOUND THERAPY AS AN INTERVENTION TO IMPROVE PHONOLOGICAL AWARENESS: CASE STUDY ON A CHILD WITH PHONOLOGICAL DISORDER - Lucky Ade Sessiani (Universitas Pendidikan Ganesha, 2018)
Phonological awareness is ability to segment the syllables and phonemes heard in speech. It is also the most important behavioral index to measure the development of reading skill. Children who had problems or impairments in phonological awareness will perform high-risk for reading skill mastery which is the most important skill in early education level. The current study aims to evaluate the effect of Word-Sound Therapy in improving phonological awareness and speech production in single word segment level. The subject of the study is a child, 5 years of age, who met the diagnostic criterias for Phonological Disorder according to Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR). The Word-Sound Therapy is used as an intervention which include series of phonological awareness tasks and inserting the speech production training between the phonological awareness activities to improve phonemic awareness. This research is using a multiple baseline across behavior design. The qualitative data analysis was conducted using behavioral approach, Response Antecedents Consequences-Strength (RAC-S). Visual inspection was also used to observe the emergence of target behaviors. Result showed that Word-Sound Therapy is improving child’s ability in identifying similarity and analyze the last phoneme in words. Result also showed that this therapy could be used for children at minimum 5 years of age, had normal IQ, and needs a phonological awareness intervention especially focused in rhyme detection and last phoneme isolation.